Determinan Kejadian Gastroesophageal Reflux Disease (GERD) pada Mahasiswa Administrasi Kesehatan: Pendekatan Theory of Planned Behavior - Yasinta Indah Widyaningsih; Rezki Ramdani; Salwah Suardi (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Background: High health literacy among students often contradicts actual Gastroesophageal Reflux Disease (GERD) management behavior, primarily due to intense academic pressure. This study aims to analyze the determinants of GERD management behavior using the Theory of Planned Behavior (TPB) framework among Health Administration students.  Methods: A cross-sectional study was conducted in January 2026 involving 318 students selected via consecutive sampling. Variables including attitude, subjective norms, perceived behavioral control, and intention were measured using validated Likert-scale questionnaires. Data were analyzed using multiple linear regression to determine the influence of each TPB construct.  Results: This study found that the prevalence of GERD symptoms among students was 61.6%, indicating that more than half of the respondents experienced reflux symptoms. The TPB model significantly influenced management intention simultaneously (p=0.000; R2=0.542). Perceived behavioral control emerged as the most dominant determinant (p=0.000; β=0.421), followed by attitude (p=0.000; β=0.382) and subjective norms (p=0.012; β=0.114). Furthermore, a distinct behavioral gap was identified regarding sleep deprivation driven by academic assignments, which hindered effective symptom management.  Conclusion: Perceived behavioral control is the primary driver of GERD management intention. Academic institutions are encouraged to re-evaluate workload distributions and foster a campus ecosystem that actively facilitates healthy lifestyle choices to bridge the gap between knowledge and behavior.